School learning climate in the lens of parental involvement and school leadership: Lessons for inclusiveness among public schools - Alinsunurin, Jason P. (Animo Repository, 2020)
Prior literature has shown that school learning climate is critical in helping individual learners meet their educational objectives. In this paper, the role of parental involvement in shaping the school learning climate is explored within a multilevel and hierarchical modeling framework using data from the 2015 PISA round. As the schools’ social and relational character, we find that reducing learning barriers is a critical challenge for school leadership. A welcoming environment for parents, as well as the effective design of effective forms of two-way communications, are positively associated with a substantial reduction in the barriers to improving teacher management’s learning climate. We also find that public schools facing social and educational inclusiveness challenges can dramatically enhance their learning environment by activating specific parental involvement mechanisms. Similarly, principal’s leadership in framing and communicating goals and curricular development to the school is also found to be significant for inclusiveness. However, parental involvement is also found to have potential tensions with school management. The worsening of the learning climate may arise due to pressures brought about by laws requiring parental involvement in schools. Because the learning climate is composed of a wide variety of relationships between and within schools, this work demonstrates that parental involvement is an integral part of school leadership and the school improvement process. Further research attention is encouraged to understand the tensions between teacher roles, principal leadership, and parental involvement through employing other quantitative or qualitative research designs. Because the learning climate is composed of a wide variety of relationships between and within schools, we argue that parental involvement is an integral part of the discourse of school leadership and school improvement process. This work also encourages further research attention to understand the tensions between teacher roles, principal leadership, and parental involvement through employing other quantitative or qualitative research designs.